Why do past disabilities still haunt the newly healthy? - Umut Oguzoglu (Review of Economic Analysis (REA), 2020)
A dynamic labour force participation model is used to estimate the impact of disability shocks on labour force participation using a longitudinal sample drawn from the National Population Health Survey. Findings suggest that state dependence play a crucial role in how temporary disabilities can have long lasting employment effects. A disability shock that last only one period is shown to lower labour force participation up to 3 additional periods. Findings are in support of policies that promote greater labour force attachment for individuals with disabilities.
Keywords: J22; I10; C33; 330; dynamic panel data; disability; labour force participation